2019
DOI: 10.32942/osf.io/jzam3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endocrinology of thermoregulation in birds in a changing climate

Abstract: The ability to maintain a (relatively) stable body temperature in a wide range of thermal environments is a unique feature of endotherms such as birds. Endothermy is acquired and regulated via various endocrine and molecular pathways, and ultimately allows wide aerial, aquatic, and terrestrial distribution in variable environments. However, due to our changing climate, birds are faced with potential new challenges for thermoregulation, such as more frequent extreme weather events, lower predictability of clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 177 publications
(213 reference statements)
1
21
0
Order By: Relevance
“…Importantly, we found that this negative relationship was explained by within-individual plasticity. A likely mechanism is increased energetic demands associated with thermoregulation that can lead to within-individual increases in corticosterone at lower temperatures (summaries: [23,62]). In our study, temperatures at capture varied between approximately 4-27°C (electronic supplementary material, figures S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found that this negative relationship was explained by within-individual plasticity. A likely mechanism is increased energetic demands associated with thermoregulation that can lead to within-individual increases in corticosterone at lower temperatures (summaries: [23,62]). In our study, temperatures at capture varied between approximately 4-27°C (electronic supplementary material, figures S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal effects may translate environmental cues from the mother to the offspring for example via maternally transferred hormones (hereafter 'maternal hormones'), potentially increasing offspring survival in the predicted conditions (adaptive maternal effects, 1,[2][3][4]. Maternal hormone-mediated effects have been recently highlighted as a potential mechanism and source of phenotypic plasticity to respond to changing climate (5)(6)(7), yet empirical evidence is scarce. Experimental studies on hormone-mediated maternal effects have revealed increasingly contradictory results, for example, elevated maternal androgens both increasing, decreasing or having no effect on offspring growth (3).…”
Section: Introductionmentioning
confidence: 99%
“…We experimentally manipulated both egg TH levels and post-hatching nest-box temperature in a wild population of pied flycatchers. We chose to study interactions between THs and temperature variation, because both factors are involved in thermoregulation (7,20), which is crucial for early-life altricial nestlings (21).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of embryonic temperature on postnatal thermoregulation have been studied particularly in poultry since temperature fluctuations inside rearing facilities have consequences for welfare and economic return (Naga Raja Kumari and Narendra Nath, 2018). Thermal sensitivity is the greatest when the hypothalamus-thyroid-pituitary-adrenal (HTPA) axis forms (Loyau et al, 2015), in line with the modulatory role of thyroid hormones in avian thermoregulation (Ruuskanen et al, 2019). In the chicken, this commences during the middle third of embryogenesis, when even brief (2-5 h) exposure to hypo-or hyperthermic incubation alters thyroid and glucocorticoid hormone secretion in response to a thermal challenge after hatching, and results in phenotypic changes that improve chicks' capacity to deal with cold or heat at least until market age of ca.…”
Section: Birdsmentioning
confidence: 87%